Sport and recreational facilities at the objects of the tourism booking area of the cross-border tourist zone - Parzych, Krzysztof; Gotowski, Rafał (Journal of Education, Health and Sport, 2018)
This article addresses the issue of the analysis of the development of the communes of the seaside tourist zone of the Polish Baltic Coast. The analysis was carried out for all 37 coastal communes of the coastal tourist zone. A quantitative and spatial analysis of the distribution of the main tourist and leisure facilities was made based on the data of the Local Data Bank of the Central Statistical Office, taking into account the state of 2017. The sports and recreation facilities of the coastal tourist zone municipalities are characterized by a significant degree of spatial differentiation. In the distribution of sports and recreation facilities accompanying the accommodation facilities, there are clear poles of spatial concentration and areas of scarcity of sports and recreation facilities. This study analyzes the development of coastal communes of the Polish Baltic Coast in sports and recreation facilities. The analysis was made at the level of all coastal communes of the coastal tourist zone. For the purposes of this study, coastal gminas have taken into account those that have direct contact with the coastline of the Baltic Sea. Ogółerm was included in the study of 32 coastal communes, part of municipalities, urban-rural part and typical rural communes. The CSO data on the number of objects of the broadly understood sports and recreation facilities of all coastal communes in Poland were used as the source material for achieving this goal. The analysis was made for 2017. The main areas of concentration of development facilities are connected with the municipalities with the best-developed base of accommodation facilities and the largest turnout of tourist traffic (Kołobrzeg, Rewal, Świnoujście, Władysławowo (commune), Łeba, Ustka, Mielno. There is a tendency to concentrate sports and recreation facilities in communes where, in addition to the typical recreational function of tourism, spa tourism (Kołobrzeg, Świnoujście) plays an important role as well as in metropolitan municipalities (Gdańsk, Gdynia). Lack of sports and recreational development or its very limited development clearly corresponds to a shortage in terms of accommodation facilities and other elements of the broadly understood tourism development. The worst equipped with sports and recreation facilities are located on the outskirts of the main development and tourism poles (Wicko, Smołdzino, Kosakowo, Międzyzdroje (rural commune), Kamień Pomorski (rural commune), Będzino, Choczewo